Long-Term Follow-up of Hypophosphatemic Bone Disease Associated With Elemental Formula Use: Sustained Correction of Bone Disease After Formula Change or Phosphate Supplementation. (October 2020) - Eswarakumar, Abigail S.; Ma, Nina S.; Ward, Leanne M.; Backeljauw, Philippe; Wasserman, Halley; Weber, David R.; DiMeglio, Linda A.; Imel, Erik A.; Gagne, Julie; Cody, Declan; Zimakas, Paul; Topor, Lisa Swartz; et al.
In this article, we describe the long-term outcomes of children who were previously reported to have developed hypophosphatemic bone disease in association with elemental formula use. An extended chart review allowed for an updated report of 34 children with regard to severity/duration of bone disease, extent of recovery, and time to correction using radiology reports and biochemical data. After implementation of formula change and/or phosphate supplementation, we found that serum phosphorus concentration increased and serum alkaline phosphatase activity decreased in all patients, normalizing by 6.6 ± 4.0 (mean ± SD) months following diagnosis. The decrease in serum alkaline phosphatase from diagnosis to the time of correction was moderately correlated with the concurrent increase in serum phosphorus ( R = 0.48, P < .05). Age at diagnosis significantly correlated with time to resolution ( R = 0.51, P = .01). This study supports the earlier report that bone disease associated with hypophosphatemia during elemental formula use responds to formula change and/or phosphate supplementation.